Typologies of Female Transformative Leadership in Balinese Tourism Villages: A Social Representation Perspective - L.G.L.K. Dewi; Yayu Indrawati; Wayan Citra Juwitasari; I Putu Andre Adi Putra Pratama (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This study analyzes the transformative typologies of female leadership in Balinese tourism villages through the lens of Social Representation Theory. Despite their vital role in community-based tourism, women remain underrepresented in formal governance due to patriarchal norms. Employing a qualitative phenomenological design, the study examines the lived experiences of three key female leaders in Tista, Sayan, and Klecung. The findings identify three distinct typologies: Environmental Awareness Leadership (ecological stewardship), Professionalized Leadership (digital and managerial competence), and Community Empowerment Leadership (cultural and economic collectivism). Through these roles, women reconstruct their social representations shifting from domestic figures to strategic public actors by re-anchoring leadership within local cultural values. This research contributes to gendered tourism scholarship by reconceptualizing Balinese women not merely as agents of change, but as "custodians of change," capable of synergizing cultural preservation with modern tourism management.